Vegetation and Seed Banks on Ex-manganese Mining in Kaubele Village Biboki Moenleu District - Wilda Lumban Tobing; Kamaluddin Kamaluddin; Marinus Kofi (Agrosains : Jurnal Penelitian Agronomi, 2023)
Mining activities are required to carry out reclamation. Reclamation efforts are aimed at restoring the condition of the mined land. The manganese mine in Kaubele Village has been carried out since 2011 but there has been no clear reclamation effort, causing the land to be abandoned. The study aimed to determine the vegetation and seed banks found on former manganese mining land in Kaubele Village, Biboki Moenleu District. This activity was carried out in July - December 2022 on former manganese mining land in 2010 and 2018. Vegetation was collected using a purposive sampling method. At each observation location, 5 main points were taken. Each point at each location is spread by 250 points with a 2 m x 2 m plot. The soil was taken at a depth of 0-20 cm and an area of 30 cm x 30 cm. Furthermore, it is placed in the nursery media for 3 months to find out the vegetation that grows. Vegetation and seed banks were analyzed based on species density, relative density, species frequency, relative frequency, and important value index. Vegetation analysis is a step in determining plants to restore ex-mining land. The vegetation in 2018 had more species compared to 2010. At both locations, there were the same 3 plants, namely Cynodon dactylon L. with an IVI of 21.421% (2010) and an IVI of 17.605% (2018), Chromolaena odorata L. with an IVI of 10.409% (2010) and IVI of 9.125% (2018), and Malvella leprosa (Ortega) krapov. with an IVI of 8.097% (2010) and an IVI of 7.031% (2018). Analysis of seed banks shows that there are 7 similar seeds found in different mining locations with respective IVI of Dactyloctenium aegyptium L. 78.550 % (2010) and 14.169 % (2018), Chloris virgata Trin 13.113 % (2010) and 8.986 % (2018), Panicum virgatum L. IVI 20.384 % (2010) and 46.834 (2017). (2018), Synedrella nodiflora L. IVI 22.068 % (2010) and 14.169 (2018), and Phyllanthus urinaria L. IVI 13.177 % (2010) and 12.957 % (2018).